Guía metodológica docente para trabajar los ejes transversales en los bloques curriculares de primer año de educación básica - Jácome Ruiz, Mercedes de Jesús (2015)
Throughout of the professional experience it has been possible to demonstrate what little importance it´s been given to the crosscut axes of the curriculum in the teaching and learning process. The curriculum of the first year of basic education, raises the crosscut axes that responds to different social problems, all of which must be met throughout the entire curriculum projection, for which it was considerable importance to know the student group the crosscutting is directed too, so it has been researched the development of children aged 5-6 years in the different areas such as: cognitive, affective social, language and motor, plus the initial education methodologies and theories of learning. Thinking about innovation of the pedagogical methodologies within in the classroom, we propose interesting activities as an interactive tool between teachers and students based on constructivism and discovery learning, where the crosscut axes are linked to curricular blocks, components and different skills, allowing children to become aware about the social issues that that need to be addressed from the earliest years of basic education. So therefore the Teacher in this work finds support to facilitate their pedagogical planning based on the crosscut axes, based on the curricular structure proposes curriculum strengthening the updating of the first year of basic general education pretending to contribute to the formation of children in the recognition and respect for different cultural manifestations in Ecuador, also a formation of a democratic citizenship, plus a commitment to environmental care, the assimilation of different food habits and recreation, as well as the care and appreciation of their own body.